Are sore throat patients who hope for antibiotics actually asking for pain relief? - van Driel, M; De Sutter, A; Deveugele, M; Peersman, W; Butler, C; De Meyere, M; De Maeseneer, J; Christiaens, T (2006)
PURPOSE: Antibiotics are still overprescribed for self-limiting upper respiratory tract infections such as acute sore throat, and physicians mention patient's desire for antibiotics as a driving force. We studied patients' concerns when visiting their family physician for acute sore throat, more specifically the importance they attach to antibiotic treatment and pain relief. METHODS: Family physicians in 6 peer groups in Belgium participated in an observational postvisit questionnaire survey. Patients aged 12 years and older making an office visit for acute sore throat were invited to indicate the importance of different reasons for the visit. RESULTS: Sixty-eight family physicians provided data from 298 patients. The 3 most frequently endorsed reasons for visiting the physician were examination to establish the cause of the symptoms, pain relief, and information on the course of the disease. Hopes for an antibiotic ranked 11th of 13 items. Patients who considered antibiotics very/rather important valued pain relief significantly more than patients who considered them little/not important (P <.001). Patients who hoped for antibiotics felt more unwell (P <.001), had more faith in antibiotics to speed recovery (P <.001), and were less convinced that sore throat was a self-limiting disease (P <.012). A multivariate model, adjusted for age, sex, and educational status, showed that the desire for pain relief is a strong predictor of the hope to receive a prescription for antibiotics. CONCLUSION: Our study suggests that patients with acute sore throat and who hope for antibiotics may in fact want treatment for pain. Trials are needed to test whether exploring patients' expectations about pain management and offering adequate analgesia can assist physicians in managing sore throats without prescribing antibiotics.